Comparison of different gene addition strategies to modify placental derived-mesenchymal stromal cells to produce FVIII - Ramamurthy, Ritu M.; Rodriguez, Martin; Ainsworth, Hannah C.; Shields, Jordan; Meares, Diane; Bishop, Colin; Farland, Andrew; Langefeld, Carl D.; Atala, Anthony; Doering, Christopher B.; Spencer, H. Trent; Porada, Christopher D.; et al. (Frontiers in Immunology, 2022)
Placenta-derived mesenchymal cells (PLCs) endogenously produce FVIII, which makes them ideally suited for cell-based fVIII gene delivery. We have previously reported that human PLCs can be efficiently modified with a lentiviral vector encoding a bioengineered, expression/secretion-optimized fVIII transgene (ET3) and durably produce clinically relevant levels of functionally active FVIII. The objective of the present study was to investigate whether CRISPR/Cas9 can be used to achieve location-specific insertion of a fVIII transgene into a genomic safe harbor, thereby eliminating the potential risks arising from the semi-random genomic integration inherent to lentiviral vectors. We hypothesized this approach would improve the safety of the PLC-based gene delivery platform and might also enhance the therapeutic effect by eliminating chromatin-related transgene silencing. We therefore used CRISPR/Cas9 to attempt to insert the bioengineered fVIII transgene “lcoET3” into the AAVS1 site of PLCs (CRISPR-lcoET3) and determined their subsequent levels of FVIII production, comparing results with this approach to those achieved using lentivector transduction (LV-lcoET3) and plasmid transfection (Plasmid-lcoET3). In addition, since liver-derived sinusoidal endothelial cells (LSECs) are the native site of FVIII production in the body, we also performed parallel studies in human (h)LSECs). Our results demonstrate that PLCs and hLSECs can both be transduced (LV-lcoET3) with very high efficiency and produce high levels of biologically active FVIII. Surprisingly, both cell types were largely refractory to CRISPR/Cas9-mediated knockin of the lcoET3 fVIII transgene in the AAVS1 genome locus. However, successful insertion of an RFP reporter into this locus using an identical procedure suggests the failure to achieve knockin of the lcoET3 expression cassette at this site is likely a function of its large size. Importantly, using plasmids, alone or to introduce the CRISPR/Cas9 “machinery”, resulted in dramatic upregulation of TLR 3, TLR 7, and BiP in PLCs, compromising their unique immune-inertness. Although we did not achieve our primary objective, our results validate the utility of both PLCs and hLSECs as cell-based delivery vehicles for a fVIII transgene, and they highlight the hurdles that remain to be overcome before primary human cells can be gene-edited with sufficient efficiency for use in cell-based gene therapy to treat HA.